APPROACHES TO STUDYING THE MOTHERLAND IMAGE IN THE SOCIAL CONCEPT SYSTEM OF NOWADAYS YOUTH - Mikhail V. Tarasov (Вестник Северо-Кавказского федерального университета, 2022)
The item offers a description of the approaches developed in the social sciences and employed to analyze the role and place of the Motherland image in the social representations of the youth.